Milk-derived anti-infectives and their potential to combat bacterial and viral infection. (June 2021) - Morrin, Sinead T.; Buck, Rachael H.; Farrow, Michael; Hickey, Rita M.
Graphical abstract: Highlights: Human milk contains bioactive ingredients which function to protect against infection. Bovine milk contains anti-infective components. Mechanisms of action of anti-infective milk components. Milk components decrease the risk of infection by bacteria and viruses. Abstract: Breastfeeding positively influences infant growth while providing protection against many diseases. Breast milk provides the ideal balance of nutrients for the infant and contains countless bioactive ingredients such as immunoglobulins (antibodies), fatty acids, oligosaccharides and others which function to protect against infection. Many of the anti-infective properties ascribed to breast-milk are not yet available to formula-fed infants. Infant milk formulas are predominantly based on bovine milk, which in some cases contain much lower concentrations of bioactives. However, bovine milk does contain a number of components which share homology with human milk bioactives which could imply common functionalities. Therefore, value may lie in extracting and concentrating select bovine milk components with a view to supplementing infant formula. This review will discuss the mechanisms of action of anti-infective milk components and their ability to decrease the risk of infection through their interactions with both bacteria and viruses.